Progress in diagnostic and treatment of age-related macular degeneration - Stankiewicz, Andrzej; Figurska, Małgorzata (Przewodnik Lekarza/Guide for GPs, 2011)
Opitcal coherence tomography (OCT) is diagnostic method that allows the analysis of the retinal structure by means of high-resolution tomographic cross-sections of the retina. Whereas fluorescein and indocyanine angiography allow visualization of the retinal epithelium layer and chorioretinal vessels, OCT may helps in diagnosis and follow-up in many internal retinal layers conditions. Ultrasound B-mode examinations have a resolution of about 150 µm while OCT yields a 10 µm resolution. Opitcal coherence tomography makes it possible to detect and measure morphological changes, retinal thickness, retinal volume, thickness of retinal nerve fiber layer and various parameters of the optic disc. Vascular endothelial growth factor A (VEGF-A) is a major factor implicated in choroidal neovascularization (CNV) and therefore a target for therapeutic agents in wet age related macular degeneration (AMD). Ranibizumab (Lucentis) binds all active VEGF-A isoforms and degradation products, penetrates all retinal layers to reach target tissue, is rapid eliminated from the body and low immunogenecity is characterized for it.